PELATIHAN BINCANG LITERASI DAN SAINS SEBAGAI UPAYA MENINGKATKAN MINAT BACA SISWA KELAS X DI SMAN 1 MENGWI - I Made Subrata; I Gusti Ayu Rai; Ni Luh Putu Tejawati (Jurnal Pengabdian Kepada Masyarakat Widya Mahadi, 2026)
This community service activity aims to increase reading interest among 10th-grade students through literacy and science discussion training at SMA Negeri 1 Mengwi. The challenges faced by the partners included the difficulty of developing literacy habits in students while studying at home, low student reading interest, and limited literacy and science learning resources available to teachers. The activity was implemented through five stages: outreach, training, technology implementation, mentoring and evaluation, and program sustainability. The training included interactive discussions, shared reading, presentations, and the use of digital media as learning resources. The results showed that the literacy and science discussion training increased student participation in reading activities, gradually developed literacy habits, and improved students' ability to understand and convey information critically. Furthermore, teachers gained new insights into utilizing more varied and innovative learning resources through the use of digital learning resources. Thus, literacy and science discussion training can be an effective strategy for strengthening literacy culture and increasing student reading interest in schools.